New species of the genus Klinckowstroemia Baker &Wharton from Mexico (Acari: Mesostigmata: Trigynaspida: Klinckowstroemiidae) - Villegas-Guzman, Gabriel A.; Pérez, Tila M.; Reyes-Castillo, Pedro (Zootaxa, 2009)
Ten new species of the genus Klinckowstroemia are described from passalid beetles (Coleoptera: Passalidae) collected in eastern and southern Mexico. The new species are Klinckowstroemia bifurcata sp. nov., K. hunteri sp. nov., K. valdezi sp. nov., K. montanoi sp. nov., K. brevimarginata sp. nov., K. rectimarginata sp. nov., K. franckei sp. nov., K. santibanezi sp. nov., K. ballesterosi sp. nov. and K. cristinae sp. nov. In some cases two species of Klinckowstroemia occurred on a single individual beetle and in one case an individual specimen of Odontotaenius zodiacus carried three species of mites: K. hunteri, K. bifurcata and K. valdezi. Eleven species of passalid beetles are new hosts for Klinckowstroemia. The beetle species associated with the most species of mites was Odontotaenius zodiacus, with six species; the other beetle species carried one or two mite species each. Mites were found in three areas of the passalid’s body: the coxae, the mesoepisternum and the humeri. Some species of Klinckowstroemia were found on more than one host species: K. valdezi and K. santibanezi were associated with four and three species of passalids respectively. This work increases the number of described species of the genus Klinckowstroemia from 14 to 24 species. The number of species of passalid beetles associated with this mite genus increased from 22 to 33.